Estrategias didácticas para mejorar el rendimiento de los estudiantes de educación regular con dificultades de dislalia en la escuela fiscal matutina “Ayúdanos A Empezar” del cantón Babahoyo, provincia de Los Ríos. - Jaramillo Almeida Irlanda Geomar (2015)
This document details the research carried out has identified the teaching strategies to improve the performance of regular education students with difficulties dislalia, who are educated in the Fiscal Morning "Start Help" School of the canton Babahoyo, Los Rios province. The study analyzed the skills and psychomotor skills that students develop dislalia problems in the teaching process, considering the four macro language skills. The age of students is under investigation for 5-12 years and has determined that children with dislalia necessarily require that teachers use special instructional strategies for efficiently linking phoneme and grapheme, this is achieved with pedagogy inclusive but using specialized teachers using an educational planning. The study culminates in the design of a teaching guide to apply appropriate teaching strategies, including how to develop breathing exercises, tongue, jaw, which lead to one goal: academic performance of students.